Significance of Low Muscle Mass on Arterial Stiffness as Measured by Cardio-Ankle Vascular Index - Park, Hyo Eun; Chung, Goh Eun; Lee, Heesun; Kim, Min Joo; Choi, Su-Yeon; Lee, Wonjae; Yoon, Ji Won (Frontiers in Cardiovascular Medicine, 2022)
Aim A link between low muscle mass and arterial stiffness are not always consistent. In this study, we aimed to evaluate the clinical significance of low skeletal muscle mass in relation to arterial stiffness, measured by cardio-ankle vascular index (CAVI). Methods A total of 2561 asymptomatic Korean subjects who had bioelectrical impedance analysis and CAVI were included for analysis. Using appendicular muscle mass (ASM), class I sarcopenia and class II sarcopenia were defined as ASM% beyond 1 standard deviation (SD) and 2SD below the gender-specific mean of healthy young Korean adults. Results Compared to normal, CAVI was significantly higher, but the number of patients with low ankle brachial index (ABI) was not significantly different (p<0.001 for CAVI, p=0.078 for ABI). Class I and II sarcopenia showed an independent and significant association with CAVI (Estimate 0.148, standard error 0.043, p<0.001, Estimate 0.304, standard error 0.073, p<0.001 for class I and II sarcopenia respectively, adjusted for age groups, gender, body mass index≥25, hypertension, diabetes, hypercholesterolemia and smoking). Conclusion Low muscle mass is independently and significantly associated with increasing CAVI, and should be considered when managing asymptomatic subjects for assessing the risk of atherosclerosis.